A Survey of User-Centered System Design for Supporting Online Collaborative Writing - Nani Sri Handayani (Intelektual Pustaka Media Utama, 2013)
Collaborative Writing (CW) is a new emerging issue in education that must be addressed interdisciplinary. Nowadays there are a lot soft ware that can be use to support and enhance the collaboration in group writing. This paper presents the discussion about the recent user centre system design for supporting collaborative writing. Based on the taxonomy and collaborative writing and the problems appear in collaborative writing, we will proposed the required design of the User-Centered System Design (UCSD) for CW software. The last part of this paper will be dedicated to examine the recent available CW soft wares based on the required designed proposed